African women in Iceland : cultural conflict and social adjustment - Patience Adjahoe Karlsson (2010)
This thesis draws on existing literature, personal experience and through interview will address the issues of cultural problems faced by African women in Iceland when adjusting into the Icelandic society. It will first explore some of the general issues faced by foreign women in Iceland. I will explore the relation between culture and identity with the focus on independent and interpedently self concepts. Whilst it is known that foreign women are particularly underprivileged in general, the key thesis is that African women in Iceland are particularly underprivileged, especially in the areas of employment and education due to couple of aboriginal African cultural factors. The thesis describes and analyses the cultural difficulty that African women face in general in adjusting in Icelandic society and in particular in relations to education. The question is, what measures can be taken in understanding and helping the African woman to adjust in the Icelandic society in a positive way? I will look at some general issues faced by African women in Iceland and investigate some psychological theories of personal identity, identity, culture, migration, and Self concepts with a focus on some aboriginal African culture with regards to women. An interview study will be conducted with the participation of 5 African women living in Iceland. Those interviews will be analysed in relation to its consequence for course of action. I will also suggest short-and long-term strategies that could help improve the lives of these African women and their children as well. I will then draw conclusions that African women can adjust culturally well in the Icelandic society, and can contribute even more positively with the right measures in regards to education. If they are given an equal opportunity to education in terms of language, and breaking the cultural barrier they will be better equip to contribute in a meaningful way. That is why it's so important to offer educational opportunity to the African women in a language that she ...